2019
DOI: 10.1159/000499039
|View full text |Cite
|
Sign up to set email alerts
|

Thiamine Substitution in Alcohol Use Disorder: A Narrative Review of Medical Guidelines

Abstract: Aims: Patients with alcohol use disorder (AUD) frequently suffer from cognitive deficits ranging from mild symptoms to most severe forms. Wernicke encephalopathy (WE), caused by thiamine deficiency, is a potentially fatal syndrome characterized by the clinical triad of ophthalmoplegia, ataxia, and confusion. WE frequently presents in patients with AUD and, if left untreated, can progress to Wernicke-Korsakoff syndrome, which constitutes severe anterograde amnesia, confabulation, and behavioral abnormalities. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…Furthermore, hardly any evidence-based recommendations exist on a more general use of thiamine as a preventative intervention in individuals with alcohol use disorder. [ 13 ] There are very few studies that have evaluated the dose and duration of thiamine for WKS, but higher doses may result in a greater response. [ 6 14 ] With thiamine administration rapid improvement is seen in eye movement abnormalities (improve within days or weeks) and ataxia (may take months to recover), but the effects on memory, in particular, are unclear.…”
Section: Neuropsychiatric Syndromes Associated With Thiamine Deficiencymentioning
confidence: 99%
“…Furthermore, hardly any evidence-based recommendations exist on a more general use of thiamine as a preventative intervention in individuals with alcohol use disorder. [ 13 ] There are very few studies that have evaluated the dose and duration of thiamine for WKS, but higher doses may result in a greater response. [ 6 14 ] With thiamine administration rapid improvement is seen in eye movement abnormalities (improve within days or weeks) and ataxia (may take months to recover), but the effects on memory, in particular, are unclear.…”
Section: Neuropsychiatric Syndromes Associated With Thiamine Deficiencymentioning
confidence: 99%
“…Thiamine therapy is safe and results in rapid clinical improvement of acute Wernicke's encephalopathy [17]. Therapeutic dosage recommendations vary from 50 mg/ day for 3 days (US guidelines) up to 500 mg every 8 h for 3-5 days followed by dosage tapering until clinical improvement (British and German guidelines) [18]. For prophylaxis, low-dose substitution is recommended for hospitalized AUD patients (100 mg/day) if they appear to be malnourished, but not routinely for all asymptomatic AUD patients.…”
Section: Therapy Of Suspected Aws In the Perioperative Settingmentioning
confidence: 99%
“…Neuropathological correlates are lesions in the periventricular region, diencephalon, midbrain, hypothalamus, and DOI: 10.1159/000507595 cerebellar vermis. Autopsy studies suggest signs of Wernicke's encephalopathy in 0.4-2.8% of the population and in 12.5% of persons with AUD [18]. As in AWS, symptom variability and other overlapping manifestations of the primary hospitalization disease, such as traumatic brain injury, sepsis, or stroke, can complicate the diagnosis.…”
mentioning
confidence: 99%
“…Some categories of patients, such as chronic, alcohol consumers, which are largely prevalent in western countries, being present in nearly 30% of hospital admissions, are at higher risk of thiamine deficiencies—these patients are at particularly high risk of refeeding syndrome and its worst neurologic complication, the Wernicke encephalopathy. A recent review of the literature confirmed the importance of administering intravenous thiamine to these patients in order to prevent severe sequelae [107]. The recommended doses ranged from 50–100 mg/day to 250–500 mg 3 times a day.…”
Section: Micronutrient Unavailability As Cause Of Deficiencymentioning
confidence: 99%